Systemic drugs with impact on osteoarthritis. (2nd October 2019) - Apostu, Dragos; Lucaciu, Ondine; Mester, Alexandru; Oltean-Dan, Daniel; Baciut, Mihaela; Baciut, Grigore; Bran, Simion; Onisor, Florin; Piciu, Andra; Pasca, Roxana D.; Maxim, Andrei; Benea, Horea
Abstract: Articular cartilage has a complex structure and metabolism which allow for a proper movement within joints. Nevertheless, several systemically administered pharmacological agents have been proved to improve the anabolic response in the case of cartilage lesions. Alendronate, glucosamine, chondroitin sulfate, hyaluronic acid, collagen hydrolysate, vitamin C, vitamin D, aspirin and strontium ranelate have shown positive results in clinical trials. On the other hand, calcitonin, risedronate, doxycycline, and celecoxib did not slow the progression of cartilage lesions in clinical trials. Other systemic drugs or supplements such as teriparatide, leptin, zoledronic acid, bevacizumab, atorvastatin, omega-3 fatty acid, naringin, MSM, selenium, zinc, magnesium, resveratrol, donepezil, naproxen, etodolac, ursodeoxycholic acid (UDCA), lithium chloride, and rebamipide showed positive results in in vitro and animal studies but clinical trials are needed to confirm the positive impact on cartilage repair. A number of molecules, not currently available on the market, have also shown promising results in cartilage healing, such as licofelone, sclerostin, cyclopamine, cyclodextrin polysulfate, AG-041R, osteoprotegerin, rhMK, β-cryptoxanthine, NF-κb essential modulator binding domain (NBD), TGF-β-neutralizing antibody, osteogenic protein-1 (BMP-7), fibroblast growth factor 2 (FGF2), and RhBMP-2. Currently available systemic drugs that impair cartilage healing are represented by corticosteroids, vitamin A, and fluoroquinolones.